ESTIMASI RISIKO KERUGIAN EKONOMI AKIBAT BANJIR ROB MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN PENJARINGAN, JAKARTA UTARA - Setyawan Purnama; Muh. Aris Marfai; Dini Feti Anggraini; Ahmad Cahyadi (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2015)
ABSTRACT As a coastal area, North Jakarta face global climate change i.e sea level rise. This phenomena can cause some negative impact to the usage of the area. The objectives of this research is to estimate economic risk caused rob flood from sea with some scenariosof sea water level. The development of flood rob mapping method incoastal area is carried out by neighbourhood operation in Geograhic Information System (GIS) based raster. Economic risk analysis is carried out by overlay of Flood Hazard Map in some scenarios and Land Use Map in certain economic value.The result of research show that economic risk that caused by flood rob 30 cm high is Rp 424.318.821.500,00. Economic risk with 115 cm flood rob high is 2.934.277.188.000,00, whereas economic risk with 200 cm flood rob high is Rp 4.758.739.166.000,00. High risk area is dominated by business area (67,76%) and reguler settlement (24,66%). Key words : rob flood, neighbourhood operation, North Jakarta